Eksplorasi Geomarine untuk Identifikasi Logam Tanah Jarang untuk Mendukung Industri Pertahanan: Studi Kasus Perairan Sabang - Lestari, Filya Rizky; Saputra, Indra Adhitiya Rama; Imastuti; Prayoga, Bagas Arya (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2025)
The strategic importance of national defense is closely related to natural resources, strategic material reserves, particularly Rare Earth Elements (REE), and the national defense industry, which is crucial for achieving defense independence. However, the exploration of REE in Indonesia has not been optimally conducted despite its vast geological potential. This research focused on mapping the distribution of REE in the Sabang Waters by applying geomarine exploration methods supported by seismic data analysis and sediment sampling. The analysis utilized seismic facies interpretation within a quantitative framework. Findings revealed a spatial association between REE distribution and geological structures influenced by volcanic activity, particularly fumaroles. These geological features potentially indicate new REE-bearing zones in shallow marine environments. This association is proposed as a new approach to REE exploration in marine tectonic settings. The research highlights the relevance of integrating remote sensing and geological data in mapping strategic minerals to support defense industry resilience.